Eighteen-month follow-up of a play-based intervention to improve the social play skills of children with attention deficit hyperactivity disorder - Wilkes-Gillan, Sarah; Bundy, A.; Cordier, Reinie; Lincoln, M. (Wiley-Blackwell Publishing Asia, 2014)
Background/aim: There is a well-documented need for interventions to successfully address the social difficulties of children with attention deficit hyperactivity disorder. This study aimed to further the development of a previously conducted pilot of a play-based intervention. To achieve this, children’s social play outcomes pre–post and 18-month following the intervention were examined by raters unaware of the study’s purpose. Additionally, parents’ experiences of the intervention were explored. Methods: Participants included five children with attention deficit hyperactivity disorder who had participated in a play-based intervention and their typically developing playmates; parents of children with attention deficit hyperactivity disorder also participated. Children and their playmates attended an 18-month follow-up play session and parents participated in semi-structured interviews. The Test of Playfulness was used to measure children’s play outcomes in the context of social play with a peer, pre–post and 18-months following the intervention. Wilcoxon signed-ranks (Z) and Cohen’s-d were used to measure effect. Thematic analysis was used to analyse reoccurring themes from parents’ interviews.Results: Children’s social play outcomes improved pre–post intervention (Z = 2.02; P = 0.04; d = 1.6) and were maintained 18-month post intervention (Z = 0.14; P = 0.89; d = -0.4). Core themes included: the intervention as an enjoyable experience, a common language for talking about play/social interactions, an observable change in children’s skills, transference of skills and the need for support to refresh learnt lessons over time. Conclusions: The intervention demonstrated preliminary and long-term efficacy in developing the social play skills of children with attention deficit hyperactivity disorder. Further research is required to optimise intervention feasibility and parent involvement prior to conducting a large-scale research.